1982
DOI: 10.1002/ajh.2830130306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of divalent cations on the conversion of fibrinogen to fibrin and fibrin polymerization

Abstract: Effects of divalent cations on fibrinogen and its reaction with thrombin were re-examined and correlated to improve definition of mechanisms underlying the acceleration of clot formation by the ions. The rate of release of fibrinopeptides from fibrinogen was not affected by any of the specific ions studied, but increased rates of fibrin monomer polymerization were obtained with all but magnesium ions. Maximal acceleration of monomer polymerization was observed with the divalent ions at concentration of 2.5-5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…Thus, it is possible that the fibrin monomers bind to Zn+2, thereby leading to more effective generation of fibrin gels. Such a model has been proposed for the accelerating effect of relatively high concentrations (2.5 mM) of Ca+2, Mg+', Ba+2, and Sr+2 [29] on the polymerization of fibrin. However, such work has not been reported with Zn+'.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is possible that the fibrin monomers bind to Zn+2, thereby leading to more effective generation of fibrin gels. Such a model has been proposed for the accelerating effect of relatively high concentrations (2.5 mM) of Ca+2, Mg+', Ba+2, and Sr+2 [29] on the polymerization of fibrin. However, such work has not been reported with Zn+'.…”
Section: Discussionmentioning
confidence: 98%
“…When thick fibers are dominant within the fibrin clot, it is less stiff, more porous; therefore, a fibrin clot can change easily the size and form, depending on the actual shear stress [62]. Several studies showed the multiple effects of Zn 2+ and Ca 2+ on fibrin clot formation because fibrinogen contains several binding sites for both cations [66,67]. Binding of fibrinogen to Ca 2+ enhances the kinetics of fibrin clot formation and also modifies the structure of the fibrin network; more thick fibers were polymerized [68].…”
Section: Zn2+-dependent Hemostasis and Fibrin Clot Formationmentioning
confidence: 99%
“…Interestingly, binding sites of Zn 2+ are mapped in the lateral D-globular domains, but not in the central E-domain and sites are distinct from those of Ca 2+ [74,75,76], indicating an alternative regulatory mechanism of fibrin formation. Similar to Ca 2+ , Zn 2+ also accelerates the rate of thrombin-induced fibrin clot formation, whereas this effect was not observed in the presence of magnesium (Mg 2+ ) or manganese (Mn 2+ ) [66,67], suggesting that modulation of thrombin-induced fibrin formation is specific to Zn 2+ and Ca 2+ . It has been shown that the lateral association of fibrin monomers to protofibrils is enhanced by Zn 2+ to a greater extent than Ca 2+ , and Zn 2+ induces a fibrin clot that has reduced fiber stiffness, compared to Ca 2+ -induced fibrin clot [66,75,77,78].…”
Section: Zn2+-dependent Hemostasis and Fibrin Clot Formationmentioning
confidence: 99%
“…In particular, the thrombin concentration and ionic conditions influence clot structure (7). Calcium (Ca 2+ ) facilitates Fn monomer polymerisation, thereby increasing fibre thickness (7)(8)(9), whereas chlorine opposes lateral aggregation and promotes thin fibre formation (10). These observations suggest that the ionic milieu influences Fn monomer polymerisation.…”
Section: Introductionmentioning
confidence: 99%